O IZIDU POSTHUMNE PESNIŠKE ZBIRKE ERICHA PRUNČA: Erich Prunč: Tihožitja in Besi. Celovec: Mohorjeva družba, 2019. - Čeh Steger, Jožica (Slavia Centralis, 2020)
The author of the article presents the posthumous edition of the collection Tihožitja in Besi (2019) by the Slavic scholar and linguist Erich Prunč.